Factors associated with pain and analgesic consumption following non‐surgical periodontal therapy under local anaesthesia and carried out by dental students - Schirmer, Caroline; Santos, Gabriela Otero; Rost, Júlia Franciele; Ferreira, Maria Beatriz Cardoso; Weidlich, Patrícia (Journal of clinical periodontology, 2018)
Aim Evaluate factors associated with pain and analgesic consumption following non‐surgical periodontal therapy. Materials and methods The sample consisted of 218 patients with chronic periodontitis, submitted to non‐surgical scaling and root planing under local anaesthesia at a public dental service in southern Brazil. The data collection instruments included a demographic questionnaire, as well as State‐Trait Anxiety Inventory, Corahʼs Dental Anxiety Scale, Visual Analogue Scale, Numerical Rating Scale and Verbal Rating Scale. The presence and intensity of pain were evaluated at 2, 6, 12, 24 and 48 hr after scaling and root planing. Results A total of 52.3% of the patients reported mild intensity pain at some point during the 48 hr after scaling and root planing with local anaesthesia. Smoking (PR = 1.47; 95% CI = 1.16–1.65), severe periodontal inflammation (PR = 1.31; 95% CI = 1.09–1.58) and dental anxiety (PR = 1.24; 95% CI = 1.03–1.49) were associated with postoperative pain after adjusting for age, gender and state and trait anxiety scores. Moreover, 46.8% of the subjects used analgesics at some time during the 48‐hr follow‐up period and dental anxiety was the only factor associated with postoperative analgesic use. Conclusions Smoking, severe periodontal inflammation and dental anxiety were identified as factors associated with pain after non‐surgical scaling and root planing with local anaesthesia. Dental anxiety was also a factor associated with postoperative analgesic use.